2013
DOI: 10.1371/journal.pone.0081152
|View full text |Cite
|
Sign up to set email alerts
|

Biotyping and Genotyping (MLVA16) of Brucella abortus Isolated from Cattle in Brazil, 1977 to 2008

Abstract: Brucellosis is a worldwide distributed zoonosis that causes important economic losses to animal production. In Brazil, information on the distribution of biovars and genotypes of Brucella spp. is scarce or unavailable. This study aimed (i) to biotype and genotype 137 Brazilian cattle isolates (from 1977 to 2008) of B. abortus and (ii) to analyze their distribution. B. abortus biovars 1, 2 and 3 (subgroup 3b) were confirmed and biovars 4 and 6 were first described in Brazil. Genotyping by the panel 1 revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Analysis of the panel A loci (MLVA-8) revealed four genotypes, with genotype 36 being the most common among the strains (91%, n = 86). Four strains were found to belong to genotype 28, two strains to genotype 38, and two strains to genotype 167,which has been detected earlier in Brazil [45]. Three loci that contributed to discrimination in the set of MLVA-8 were Bruce 06 (HGDI of 0.083), Bruce 11, and Bruce 55 with an HGDI of 0.082.…”
Section: Resultsmentioning
confidence: 62%
“…Analysis of the panel A loci (MLVA-8) revealed four genotypes, with genotype 36 being the most common among the strains (91%, n = 86). Four strains were found to belong to genotype 28, two strains to genotype 38, and two strains to genotype 167,which has been detected earlier in Brazil [45]. Three loci that contributed to discrimination in the set of MLVA-8 were Bruce 06 (HGDI of 0.083), Bruce 11, and Bruce 55 with an HGDI of 0.082.…”
Section: Resultsmentioning
confidence: 62%
“…The MLVA16 panel 1 profiles of both B. abortus isolates, genotypes 28 and 40 by the MLVAbank, have already been previously observed in Minas Gerais State [11]. Moreover, the comparison between MLVA16 genotypes of B. abortus biovar 3 field strain (W) and those previously described by Minharro et al [11] revealed differences restricted to hypervariable loci [panels 2A (Bruce19) and 2B (Bruce04)], suggesting a possible epidemiological link between these strains, since all were isolated in the state of Minas Gerais and were also identified as biovar 3.…”
Section: Discussionmentioning
confidence: 73%
“…The mPCR validated in the present research has identified different Brucella species and was able to discriminate the vaccine strain S19, field strain and different groups of biovars found in Brazil (MINHARRO et al, 2013). Originally described AMOS PCR can not detect biovars 3, 5, 6 and 9 and does not any internal control for DNA extraction and PCR inhibition, except when working with differentiation of vaccine samples (BRICKER & HALLING, 1995).…”
Section: Reproducibilitymentioning
confidence: 67%